Investigation of processing, microstructures and efficiencies of polycrystalline CdTe photovoltaic films and devices - Munshi, Amit Harenkumar, author; Sampath, W. S., advisor; Sites, James R., committee member; James, Susan P., committee member; Powell, Rick C., committee member; Holland, Troy B., committee member (Colorado State University. Libraries, 2017)
CdTe based photovoltaics have been commercialized at multiple GWs/year level. The performance of CdTe thin film photovoltaic devices is sensitive to process conditions. Variations in deposition temperatures as well as other treatment parameters have a significant impact on film microstructure and device performance. In this work, extensive investigations are carried out using advanced microstructural characterization techniques in an attempt to relate microstructural changes due to varying deposition parameters and their effects on device performance for cadmium telluride based photovoltaic cells deposited using close space sublimation (CSS). The goal of this investigation is to apply advanced material characterization techniques to aid process development for higher efficiency CdTe based photovoltaic devices. Several techniques have been used to observe the morphological changes to the microstructure along with materials and crystallographic changes as a function of deposition temperature and treatment times. Traditional device structures as well as advanced structures with electron reflector and films deposited on Mg1-xZnxO instead of conventional CdS window layer are investigated. These techniques include Scanning Electron Microscopy (SEM) with Electron Back Scattered Diffraction (EBSD) and Energy dispersive X-ray spectroscopy (EDS) to study grain structure and High Resolution Transmission Electron Microscopy (TEM) with electron diffraction and EDS. These investigations have provided insights into the mechanisms that lead to change in film structure and device performance with change in deposition conditions. Energy dispersive X-ray spectroscopy (EDS) is used for chemical mapping of the films as well as to understand interlayer material diffusion between subsequent layers. Electrical performance of these devices has been studied using current density vs voltage plots. Devices with efficiency over 18% have been fabricated on low cost commercial glass substrates with processes suitable for mass production. These are the highest efficiencies reported by any university or national laboratory for polycrystalline thin-film CdTe photovoltaics bettered only by researchers at First Solar Inc. Processing experiments are traditionally designed based on simulation results however in these study microscopic materials characterization has been used as the primary driving force to understand the effects of processing conditions. Every structure and efficiency reported in this study has been extensively studied using microscopic imaging and materials characterization and processing conditions accordingly altered to achieve higher efficiencies. Understanding CdCl2 passivation treatment out of this has been critical to this process. Several observations with regard to effect of CdCl2 passivation have allowed the use to this treatment to achieve optimum performance. The effects of deposition temperature are also studied in rigorous details. All of these studies have played an important role in optimization of process that lead to high efficiency thin-film CdTe photovoltaic devices. An effort is made in this study to better understand and establish a 3-way relationship between processing conditions, film microstructure and device efficiency for sublimated thin-film CdTe photovoltaics. Some crucial findings include impact of grain size on efficiency of photovoltaic devices and improvement in fill-factor resulting from use of thicker CdTe absorber with larger grain size. An attempt is also made to understand the microstructure as the device efficiency improves from ~1% efficiency to over 18% efficiency.
Keywords: cadmium telluride; renewable energy; thin-film; photovoltaics; cadmium chloride; solar energy